Antecedents of cloud ERP adoption in manufacturing industry: Nigerian SMEs context - Usman, Usman Musa Zakari; Ahmad, Mohammad Nazir; Zakaria, Nor Hidayati (2016)
Cloud ERP systems are continuously replacing the implementation of traditional ERP systems within the enterprise industry, the cloud ERP system’s ability to exploit internet’s continuity.The increased reliability of cloud infrastructures has made it economically feasible to deliver ERP systems over the internet, at less risk than that involved with traditional ERP, allowing for the transfer of maintenance and support to the vendor. Cloud ERP system also enables small and medium-sized budget organizations to access incredibly robust technology at an affordable cost, and at a low cost of ownership, with quick deployment and a fast return of investment.Manufacturing company today are faced with challenge as the world is moving faster and more connected than before, nature of world economy, growth in consumer technology, and rapidly changing and sometimes, unpredictable consumer purchasing behaviors, all brings both opportunity and risk, as a result manufacturer need to invest in the next generation of industrial automation solution.Factors that are significant to influence adoption cloud ERP in SMEs are still unclear, mainly in the context of developing countries and Nigeria in particular. Therefore, this research paper discusses various potential factors from relevant literature that would influence manufacturing SMEs to adopt cloud ERP system.